Effects of dietary mycotoxins and mycotoxin adsorbent additives on production performance, hematological parameters, and liver histology in juvenile Nile tilapia (Oreochromis niloticus) - Fornari, Darci Carlos; Peixoto, Silvio; Ksepka, Steven P.; Bullard, Stephen A.; Rossi, Waldemar; Nuzback, Dennis E.; Davis, D. Allen (Frontiers in Animal Science, 2023)
Mycotoxins are fungal secondary metabolites that can adversely affect animals consuming contaminated feeds. This 71-day feeding trial was conducted to assess the effects of dietary deoxynivalenol plus zearalenone (DON+ZEN = 1.6+0.3 ppm), and fumonisins (FUM = 15 ppm), and three adsorbent additives on the production performance, hematological parameters, and liver histology of juvenile Nile tilapia. A mycotoxin-free diet (Control) formulated to contain 35% protein and 8% lipid was spiked with either DON+ZEN or FUM using contaminated corn meals replacing portions of non-spiked corn. Subsequently, three out of four DON+ZEN- and FUM-spiked diets were supplemented (0.5%) with an adsorbent. The research was carried out in a recirculating water system (2,500 L) with a controlled temperature of (25.9±1.1°C), feeding was carried out twice a day at rates ranging from 5 to 8%. The experiment included nine treatments with five replications, each experimental unit consisting of an aquarium with a useful volume of 75-L and fifteen juvenile Nile tilapia (average initial weight of 4.0±0.1 g). Mycotoxin-spiked diets without added adsorbent supported lower final biomass and survival of Nile tilapia relative to control and adsorbent containing diets (P≤0.05). Histological examinations revealed liver inflammation evidenced by lymphocytic infiltration adjacent to pancreatic tissue in fish fed mycotoxin-spiked diets without added adsorbent. Mycotoxin contamination significantly increased HIS (hepato somatic index), which was reverted to the Control value or reduced further by adsorbent addition. Lowest and intermediate hematocrit values were observed in groups fed mycotoxin-spiked diets without and with added adsorbents, respectively. Our results reinforce the importance of using adsorbents and the need to investigate the effect of sub-lethal concentrations of mycotoxins in aquaculture feeds.